Putting people first: a multidimensional approach to health socioeconomic determinants - Barreira, Maria Esmeralda (2019)
Person Centered Healthcare aims for the involvement of patients to provide quality healthcare services based on committed healthcare professionals. This paradigm implies shared decision-making between healthcare professionals and patients involving various aspects of the patient-healthcare relation. The present work focuses on the importance of analysing healthcare services distribution considering communities’ specificities. To develop appropriate healthcare solutions that fit people needs, public health policies should be designed in a manner that involves health stakeholders, experts and the civil society. The United Nations 2030 Agenda for Sustainable Development proposes the Sustainable Development Goal 3 in order to “ensure healthy lives and promote well-being for all at all ages” which is in alignment with the Person Centered Healthcare aims. The present work proposes a tailored made index SEHVI – Socioeconomic Health Vulnerability Index – applied to Portuguese mainland population. In the scope of the principle of patient-centered healthcare services, SEHVI aggregates seven health outcomes indicators – mortality variables – and twenty-eight health determinants indicators: healthcare resources, social protection, education, water and sanitation, employment and income, air pollution, waste, land use, housing, social participation and safety variables. Data was collected from official statistical databases – INE, PORDATA and APA – and disaggregated at the municipal scale, allowing a diagnose of people’s needs and specificities at a local level. Years 2009, 2015 and 2018 were chosen to evaluate population health status. The country national score was used as the benchmark enabling the identification of vulnerable communities. The majority (72 %) of the mainland population experiences more vulnerable health conditions than the country’s average. SEHVI scores reveal a deterioration of health determinants in the period of study. Populations’ socioeconomic and environmental conditions play an important role in health outcomes, stressing the need to provide adequate healthcare services in the context of a centered healthcare approach.